2013
DOI: 10.2298/vsp1305493s
|View full text |Cite
|
Sign up to set email alerts
|

Smoking habits, knowledge about and attitudes toward smoking among employees in health institutions in Serbia

Abstract: According to the result of this survey, there are needs for more aggressive nationwide non-smoking campaigns for physicians and medical students. Experiences from countries where physicians smoke less and more effectively carry out smoking cessation practices need to be shared with Serbian physicians in order to improve their smoking behavior and smoking cessation practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
7
2
Order By: Relevance
“… 26 In Serbia, 60.7% of physicians agreed that healthcare professionals serve as role models for their patients and public. 27 However, data from a focus group interview carried out among Armenian doctors revealed that the majority of doctors believed they have no role in patients’ quitting. 28 Compared with Finnish physicians, Estonian physicians were less conscious of their role as healthy lifestyle exemplars in 2002.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In Serbia, 60.7% of physicians agreed that healthcare professionals serve as role models for their patients and public. 27 However, data from a focus group interview carried out among Armenian doctors revealed that the majority of doctors believed they have no role in patients’ quitting. 28 Compared with Finnish physicians, Estonian physicians were less conscious of their role as healthy lifestyle exemplars in 2002.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 ] All deleterious habits were reported in male subjects; smoking and consumption of alcohol were not observed in female subjects in the present study which is in contrast to some other study findings in which about 46% were female smokers. [ 15 ] This may be due to a social taboo in the Indian community which doesn’t allow Indian women to consume alcohol and smoke. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The moderately high prevalence of smoking amongst health care providers is alarming as they are setting a bad example to patients by being uncritical to this habit by rarely asking patients about their smoking and rarely advising them not to smoke ( Stojanović et al, 2013 ). This is further elaborated by a research which found out that of the physicians who smoke, 25% do not warn their patients about the risks of smoking and about 22% not always give advice to them about quitting ( Araya et al,2012 ).…”
Section: Discussionmentioning
confidence: 99%